The source of folk pedagogy and the potential of language education - Dolzhikova, Angela V. (The New Research of Tuva, 2023)
The present article, framed within the genre of a review, critically examines the pedagogical potential and significance encapsulated in the popular science publication titled “Dagylga: Tuvan Rituals of Consecration in the 21st Century” (Kyzyl, 2021), authored by a team led by Ch. K. Lamazhaa. Primarily intended for their fellow countrymen and compatriots, the Tuvans, the publication aims to disseminate invaluable insights capable of enriching their Dagylga ritual practices through borrowings and clarifications. Noteworthy is the fact that the book is available in both Russian and Tuvan languages, underscoring its accessibility and relevance to the indigenous audience.The author of the review emphasizes the scholarly significance of the conducted research, extending beyond the realms of Tuvan studies, ethnography, and the historical narrative of the diverse peoples within the Russian Federation. The reviewer particularly accentuates the research's scientific and pragmatic value in the context of ethno-pedagogy and linguistic (bilingual) education. The outcomes derived from the endeavors of Tuvan scholars pique the interest of educational facilitators, practical educators, and linguistic researchers alike. The incorporation of a bilingual text, a specialized glossary elucidating technical terminology, accompanying photographs capturing the diverse Tuvan clans performing Dagylga rituals, meticulous citations, and QR codes providing direct access to pertinent video materials, collectively underscore the comprehensive and innovative approach adopted towards the subject and object of the research.This multifaceted methodology proves instrumental, especially concerning the pedagogical engagement with students born in the digital age. As society traverses the era of digital technologies, these meticulous scholarly efforts become indispensable in fostering a nuanced understanding of Tuvan cultural practices and heritage.
Keywords: review; Tuvan studies; Dagylga; Tuva; Tuvans; folk pedagogy; religious revival